Activation states of blood eosinophils in asthma. Issue 4 (April 2014) - Johansson, M. W.
Summary Asthma is characterized by airway inflammation rich in eosinophils. Airway eosinophilia is associated with exacerbations and has been suggested to play a role in airway remodelling. Recruitment of eosinophils from the circulation requires that blood eosinophils become activated, leading to their arrest on the endothelium and extravasation. Circulating eosinophils can be envisioned as potentially being in different activation states, including non‐activated, pre‐activated or 'primed', or fully activated. In addition, the circulation can potentially be deficient of pre‐activated or activated eosinophils, because such cells have marginated on activated endothelium or extravasated into the tissue. A number of eosinophil surface proteins, including CD69, L‐selectin, intercellular adhesion molecule‐1 (ICAM‐1, CD54), CD44, P‐selectin glycoprotein ligand‐1 (PSGL‐1, CD162), cytokine receptors, Fc receptors, integrins including αM integrin (CD11b), and activated conformations of Fc receptors and integrins, have been proposed to report cell activation. Variation in eosinophil activation states may be associated with asthma activity. Eosinophil surface proteins proposed to be activation markers, with a particular focus on integrins, and evidence for associations between activation states of blood eosinophils and features of asthma are reviewed here. Partial activation of β1 and β2 integrins on blood eosinophils, reported by monoclonal antibodies (mAbs) N29 and KIM‐127, is associated with impaired pulmonary function and airway eosinophilia, respectively, in non‐severe asthma. The association with lung function does not occur in severe asthma, presumably due to greater eosinophil extravasation, specifically of activated or pre‐activated cells, in severe disease.